2019
DOI: 10.1017/jfm.2019.215
|View full text |Cite
|
Sign up to set email alerts
|

Retrogressive failure of a static granular layer on an inclined plane

Abstract: When a layer of static grains on a sufficiently steep slope is disturbed, an upslope-propagating erosion wave, or retrogressive failure, may form that separates the initially static material from a downslope region of flowing grains. This paper shows that a relatively simple depth-averaged avalanche model with frictional hysteresis is sufficient to capture a planar retrogressive failure that is independent of the cross-slope coordinate. The hysteresis is modelled with a non-monotonic effective basal friction l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 61 publications
4
31
0
Order By: Relevance
“…is used in this paper to best match experimental results. This is very close to the value h * /h stop = 1.33 measured in flows of glass beads by Russell et al (2019).…”
Section: The Effective Basal Friction Lawsupporting
confidence: 89%
See 1 more Smart Citation
“…is used in this paper to best match experimental results. This is very close to the value h * /h stop = 1.33 measured in flows of glass beads by Russell et al (2019).…”
Section: The Effective Basal Friction Lawsupporting
confidence: 89%
“…The surface velocity data for sand (Takagi et al 2011) shown in figure 11 suggest that u s = 2.35ū, which implies λ = 2.05. This is within 15 % of the value u s = 2.7ū (corresponding to λ = 2.45) measured experimentally in a thin unconfined flow of glass beads (Russell et al 2019).…”
Section: Implications For the Interpretation Of Levee-channel Depositssupporting
confidence: 82%
“…7.3. Extensions to the theory Inertial CIDR is also able to incorporate non-monotonicity of the µ(I) function (DeGiuli & Wyart 2017), which is crucial for modelling hysteretic effects, such as coexisting static and moving regions, in depth-averaged avalanche models (Daerr & Douady 1999;Pouliquen & Forterre 2002;Edwards & Gray 2015;Edwards et al 2017;Russell et al 2019). Non-monotonic µ = µ(I) functions are problematic in the incompressible µ(I)-rheology, because they imply that the theory is always ill-posed in regions of decreasing friction (Barker et al 2015).…”
Section: Comparison Of Icidr With Dem Simulationsmentioning
confidence: 99%
“…This means that the material parameters required for the depth-averaged analysis consist of the density ρ 2000 kg/m 3 and the frictional coefficient of the basal surface μ 0.27. In the simulation by the depth-average model, the common used earth pressure coefficient (Savage and Hutter 1989) is assumed to be unity, like in other recent works (e.g., Russell et al 2019).…”
Section: Landslide Propagationmentioning
confidence: 99%